Lamuri Telah Islam Sebelum Pasai - Repelita Wahyu Oetomo (Berkala Arkeologi Sangkhakala, 2008)
AbstractLamuri is known as a place in Aceh Besar, which supported by the existence of grave complex and fortress. The result of archaeological activities indicated that the gravestone in Aceh Besar is older than Samudera Pasai.